Visual inspection after acetic acid (VIA) is highly heterogeneous in primary cervical screening in Amazonian Peru. - Maribel Almonte; Catterina Ferreccio; Silvana Luciani; Miguel Gonzales; Jose M Delgado; Carlos Santos; Manuel Alvarez; Jack Cuzick; Peter Sasieni (PLoS ONE)
Background Conventional cytology (Pap) and visual inspection after the application of acetic acid (VIA) are currently used in primary screening in Peru. Studies suggest that the quality of VIA is highly variable. Over 36 000 women were screened with Pap and VIA in the TATI (Tamizaje y Tratamiento Inmediato de Lesiones Cervico-uterinas) project conducted in Amazonian Peru. Within a nested study to compare several screening techniques (C-TATI), a total of 5435 women were additionally screened with liquid-based cytology (LBC) and high-risk human papillomavirus testing (HR-HPV). We investigate the variation of positivity rates of VIA, Pap, LBC and HR-HPV in C-TATI and of VIA in the full TATI intervention. Methods At the screening visit, midwives collected three cervical samples for Pap, LBC and HC2 before performing VIA. The dispersion factor "D" (D = Pearson chi-square value/degrees-of-freedom) was used to measure the variability of tests results. Within C-TATI, the variability of positivity rates of VIA, Pap, LBC and HR-HPV was also graphically assessed with box- and scatter plots by midwife and month of screening. Funnel plots and smoothed scatter plots were used to correlate the variation of VIA by the number of examinations performed by each midwife over the full TATI intervention. Results Consistently over TATI, VIA results were highly variable, independently of the examiner, the time when the test was performed and the number of tests the examiner performed (D>6, p-values<0.001). In C-TATI, VIA results varied the most while those of HR-HPV varied the least (Ds>25, p-values<0.001 for VIA, Ds<1.6, p-values>0.05 for HR-HPV). No evidence for correlation between the number of VIAs done per midwife and the variability of VIA results was observed. Conclusion The lack of over-dispersion for HR-HPV detection suggests that the variable VIA results do not reflect true variation in underlying disease, but a lack of consistency in human judgement.